The Role of The Counseling Teacher In Developing The Social Dimensions of Children With Special Needs - Beni Azwar (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This research was carried out in MAN 2 Payakumbuh with the type of blind crew members. This study aims to determine the role of guidance counselling teachers in developing students’ social dimensions, starting with the adjustment process at school. This study uses descriptive-qualitative with the purpose of descriptive-analytic method about the role of guidance counselling teachers in developing the social dimension for ABK in three inclusive schools. The results showed that: First; social and emotional problems are basic problems for special needs, secondly; in providing guidance counselling services, guidance counselling teachers provide classical and group services by building social awareness and empathy for all students and other school residents, Third; the development of social interest is marked by the collection of monthly zakat and infaq of teachers and staff for underprivileged students, including children with special needs studying at UNP Padang and IAIN Bukittinggi.